Human resource management practices and employee performance management in Nigerian higher educational institutions - Nura, Abubakar Allumi (2014)
Previous studies on performance management system focus on one or two of its dimensions with little insight in the public sector, so also studies on human resource management practices did not attempt to use all the practices comprehensively. This study examined both individually and comprehensively the relationship between the six human resource management practices and all the four dimensions of performance management system among academics in higher educational institutions in Nigeria. The dimensions of performance management system as operationalized by this study are, organizational objective, individual objective, performance development and employee satisfaction. Human resource management practices also as operationalized by this study are procurement, development, compensation, integration, maintenance and separation. Furthermore, this study also investigated the mediating effects of employee behavior and information and communication technology (ICT) adoption on the relationship between human resource management practices and performance management system among academics in higher educational institutions in Nigeria. Data was collected from five Federal universities in the North Western Nigeria using a cross sectional study design and multimode survey strategy. 800 questionnaires were distributed to the respondents who were sampled using a multi stage sampling technique. SmartPLS SEM was used in testing the study hypotheses. The results obtained indicated that majority of the hypothesized relationships thirteen (13) out of twenty (20) direct relationships were supported. Additionally, the results of the mediation tests provided that five (5) mediating hypotheses out of twelve were significant. The outcome of this study provides a very sound insight of the study on performance management system in the public sector particularly higher educational institutions. It will also benefit the government, the policy makers and other concerned agencies in Nigeria. More so, information and communication technology and employee behaviors have been proven by this study as strategic tools that could be efficiently used by managers to effectively manage performance of their employees. This study encountered limitations such as inability to include other types of higher educational institutions like the polytechnics and colleges of education, unable to cover all the six regions in Nigeria instead focused on only one region the North West region.